2020
DOI: 10.1080/02791072.2020.1836435
|View full text |Cite
|
Sign up to set email alerts
|

Loneliness, Mental Health, and Substance Use among US Young Adults during COVID-19

Abstract: As COVID-19 converges with loneliness and addiction epidemics in the US, both public health and mental health experts forecast dramatic increases in substance use and mental health conditions. This cross-sectional study evaluated relationships of loneliness with depression, anxiety, alcohol use, and drug use during COVID-19, and assessed perceived increases in these symptoms in young adults. Between April 22 and May 11, 2020, 1,008 participants ages 18-35 were recruited through social media to a one-time, onli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
196
1
4

Year Published

2021
2021
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 269 publications
(259 citation statements)
references
References 30 publications
29
196
1
4
Order By: Relevance
“…A summary of factors associated with increased alcohol use include psychological distress related to COVID-19 [ 32 ▪ , 33 , 35 , 39 ], increased availability of free time [ 40 ], misinformation about alcohol, heavy drinking prepandemic, job loss, eating more, changes in sleep, higher anxiety and depression [ 41 44 ], living with children [ 45 ], reduced physical activity [ 46 ], loneliness, [ 47 ], cyberbullying, victimisation at work [ 33 ], lower social connectedness and having one child under the age of 18 years [ 48 ]. In a US-based online survey, increase in alcohol-related problems was independent of the amount of alcohol consumption [ 29 ].…”
Section: Text Reviewmentioning
confidence: 99%
“…A summary of factors associated with increased alcohol use include psychological distress related to COVID-19 [ 32 ▪ , 33 , 35 , 39 ], increased availability of free time [ 40 ], misinformation about alcohol, heavy drinking prepandemic, job loss, eating more, changes in sleep, higher anxiety and depression [ 41 44 ], living with children [ 45 ], reduced physical activity [ 46 ], loneliness, [ 47 ], cyberbullying, victimisation at work [ 33 ], lower social connectedness and having one child under the age of 18 years [ 48 ]. In a US-based online survey, increase in alcohol-related problems was independent of the amount of alcohol consumption [ 29 ].…”
Section: Text Reviewmentioning
confidence: 99%
“…Evidence from empirical studies has shown that loneliness is an important risk factor for a myriad of deleterious physical and mental consequences, including early mortality, cardiovascular diseases, metabolic syndrome, suicidal behaviors, depressive symptoms, and cognitive decline [3][4][5][6][7][8][9]. Similarly, during this pandemic, population-based studies have demonstrated significant associations of feelings of loneliness with increased risk of depression, anxiety, psychological distress, poor sleep, alcohol and drug use, and poor quality of life [10][11][12][13][14]. Importantly, researchers found that, compared to adults who were not lonely, lonely adults were significantly less likely to engage in a variety of individual COVID-19 preventive behaviors [15].…”
Section: Introductionmentioning
confidence: 99%
“…Physical distancing and contact reduction are causing severe stress to many people and might increase the risk of suicide. 6 In a meta-analysis of the prevalence of stress, anxiety, depression among the general population during the COVID-19 pandemic, 7 8 Further and stronger restrictions on physical and social contact could lead to a further increase in the prevalence of depression.…”
Section: Calling For Benefit-risk Evaluations Of Covid-19 Control Meamentioning
confidence: 99%